Seismic experimental assessment of steel and synthetic meshes for retrofitting heritage earthen structures. (1st November 2019) - Reyes, Juan C.; Smith-Pardo, J. Paul; Yamin, Luis E.; Galvis, Francisco A.; Angel, Christiam C.; Sandoval, Juan D.; Gonzalez, Cristian D.
Highlights: Steel welded wire meshes are effective enhancing the shear capacity of thick adobe walls. Retrofitting with meshes is more efficient for earthen walls under low axial loads. Meshes do not prevent first cracking but delay damage accumulation of earthen walls. Meshes are inefficient preventing excessive permanent drifts in earthen walls. Abstract: Thick adobe and/or rammed earth walls are common features of traditional construction from the colonial period in South America. Structures of this type have suffered extensive damage or collapse during severe and even moderate earthquakes leading to the loss of heritage landmarks and worse-yet human lives. Many retrofitting techniques have been proposed over the years for earthen construction including wire and synthetic meshes. Even though much numerical and experimental research has been conducted on the seismic behavior of earthen walls, few studies have focused on investigating the in-plane and out-of-plane response of thick full-scale specimens with and without retrofitting. This paper addresses some of those limitations by presenting experimental results of twelve 0.4 m-thick adobe and rammed earth (RE) full-scale walls under cyclic loading, as well as four 0.60 m-thick full-scale RE walls under out-of-plane dynamic loading. It was found that properly installed meshes can be very effective in enhancing the in-plane shear strength and the out-of-plane capacity of thick earthen walls by preventing premature local failures and by providing confinement after cracking, particularly for low levels of axial load. Retrofitting with meshes does not significantly change the lateral stiffness of walls and may not be adequate to preserve the architectural integrity of historic construction after a major earthquake; however, meshes enhance deformation and energy dissipation capacity of walls and ultimately protect the lives of building occupants.